2007
DOI: 10.1523/jneurosci.4393-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Lobula Plate Output Signals by DNOVS1, an Identified Premotor Descending Neuron

Abstract: Many motion-sensitive tangential cells of the lobula plate in blowflies are well described with respect to their visual response properties and the connectivity among them. They have large and complex receptive fields with different preferred directions in different parts of their receptive fields matching the optic flow that occurs during various flight maneuvers. However, much less is known about how tangential cells connect to postsynaptic neurons descending to the motor circuits in the thoracic ganglion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 47 publications
6
75
0
Order By: Relevance
“…We hypothesize that the descending visual inputs to FN type II NMNs (Haag et al, 2007;Wertz et al, 2008) are too small to generate action potentials on their own but can affect the probability that the haltere-induced PSPs become suprathreshold. Thus, the visual input can affect the neuron's action potential output only in the presence of another input, such as that from the halteres (Fig.…”
Section: The Action Potential Nonlinearity Results In a Gating-like Ementioning
confidence: 99%
“…We hypothesize that the descending visual inputs to FN type II NMNs (Haag et al, 2007;Wertz et al, 2008) are too small to generate action potentials on their own but can affect the probability that the haltere-induced PSPs become suprathreshold. Thus, the visual input can affect the neuron's action potential output only in the presence of another input, such as that from the halteres (Fig.…”
Section: The Action Potential Nonlinearity Results In a Gating-like Ementioning
confidence: 99%
“…The lobula plate is a well characterized brain center dedicated to the processing of optic flow. Their response properties to visual stimuli of many motion-sensitive tangential cells of the lobula plate and their postsynaptic descending neurons have been described (Krapp and Hengstenberg, 1996;Krapp et al, 1998;Haag et al, 1999Haag et al, , 2007Farrow et al, 2006;Joesch et al, 2008;Wertz et al, 2008Wertz et al, , 2009Borst et al, 2010;Schnell et al, 2010). From various lines of evidence, it has been concluded that the tangential cells are involved in the visual course control of the fly (Heisenberg et al, 1978;Nässel, 1981, 1982;Wehrhahn, 1983, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In the next step towards flight control, lobula plate tangential cells synapse onto descending neurons that either connect to the motor centers in the thoracic ganglion or directly innervate the neck muscles for head motion control [28,51,62,40]. As two representatives of such neurons, DNOVS1 and DNOVS2 (short for descending neurons of the ocellar and vertical system) have been recently examined in great detail [32,66,67]. Using current injection during dual intracellular recording from DNOVS-cells and various VS-cells, their connectivity to VScells was established.…”
Section: Global Optic-flow Analysis In the Lobula Platementioning
confidence: 99%